2023
DOI: 10.1152/japplphysiol.00769.2022
|View full text |Cite
|
Sign up to set email alerts
|

Muscle group-specific skeletal muscle aging: a 5-yr longitudinal study in septuagenarians

Abstract: There is some evidence that the age-associated change in skeletal muscle mass is muscle specific, yet the number of specific muscles that have been studied to form our understanding in this area is limited. In addition, few aging investigations have examined multiple muscles in the same individuals. This longitudinal investigation compared changes in skeletal muscle size via computed tomography of the quadriceps (rectus femoris, vastus lateralis, vastus medialis, vastus intermedius), hamstrings (biceps femoris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…It is also interesting to note the hamstrings muscles have a lower attenuation value (i.e., more fatty infiltration) compared to the quadriceps (Table 2 ), and the difference in attenuation values between the non‐consumers and aspirin consumers was greater in the hamstrings (+20%) compared to the quadriceps (+9%). Differences in skeletal muscle attenuation have been reported across several muscles in the Health ABC cohort (Goodpaster et al, 2001 ; Naruse et al, 2023 ). Overall, these attenuation findings do suggest some influence of chronic aspirin consumption on skeletal muscle of older individuals that needs to be investigated further.…”
Section: Discussionmentioning
confidence: 93%
“…It is also interesting to note the hamstrings muscles have a lower attenuation value (i.e., more fatty infiltration) compared to the quadriceps (Table 2 ), and the difference in attenuation values between the non‐consumers and aspirin consumers was greater in the hamstrings (+20%) compared to the quadriceps (+9%). Differences in skeletal muscle attenuation have been reported across several muscles in the Health ABC cohort (Goodpaster et al, 2001 ; Naruse et al, 2023 ). Overall, these attenuation findings do suggest some influence of chronic aspirin consumption on skeletal muscle of older individuals that needs to be investigated further.…”
Section: Discussionmentioning
confidence: 93%
“…Our discovery of asynchronous muscle growth in children aligns with two recent studies examining diverse age groups. One longitudinal study observed asynchronous muscle atrophy (reduction in muscle cross‐sectional area) in six muscle groups of 469 septuagenarians over a 5‐year period (Naruse et al., 2023 ). Another cross‐sectional study found asynchronous growth (increase in muscle volume) in four leg muscles of 118 typically developing children aged between 3 and 11 years (Peeters et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are few methodological approaches that can be used to address our overall research interest in this area. Future studies could use other MRI or CT approaches to better understand muscle composition (Goodpaster et al, 2023 ) and how that may vary among muscles (Naruse, Fountain, et al, 2023 ), both in response to aging and exercise training. Even more advanced imaging and metabolic studies could be considered, although the radioactivity may be a limitation (Fujimoto et al, 2000 ; Gondoh et al, 2009 ; Oi et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%